A nano-reactor based on PtNi@metal–organic framework composites loaded with polyoxometalates for hydrogenation–esterification tandem reactions. Issue 7 (5th February 2019) - Chen, Luning; Zhang, Xibo; Zhou, Jinhong; Xie, Zhaoxiong; Kuang, Qin; Zheng, Lansun
Abstract : A nano-reactor based on PtNi@metal–organic framework composites loaded with polyoxometalates were successfully constructed and applied to hydrogenation–esterification tandem reactions. Abstract : Tandem catalysis ( i.e., a process in which a desirable product is synthesized by a one-step process consisting of sequential reactions) has attracted intensive attention owing to its sustainable green and atom-economical characteristics. In this process, the utilization of a high-efficiency multifunctional catalyst is key. However, different functional sites integrated within the catalyst are required to be rationally designed and precisely engineered to guarantee the synergy between the catalytic reactions. Herein, a novel kind of hydrogenation–esterification tandem catalyst with metal/acid (alloy/polyoxometalates) active sites integrated within the metal–organic frameworks (MOFs) was prepared by a facile self-sacrificial template route. In this tandem catalyst, the MOF cavities served as tandem reactors, the PtNi alloy sites encapsulated within the MOF material acted as hydrogenation sites, and the solid phosphotungstic acid embedded in the MOF cavities provided esterification sites. This well-designed tandem catalyst showed outstanding activity and selectivity towards the one-step synthesis of amino-ester-type anesthetics ( e.g., benzocaine) owing to the synergistic catalysis of the metal and acid sites. Clearly, this novel tandem catalyst simplifies the traditional industry process and provides a new method to rationally construct new tandem catalysts.